Diagnostic Use of Vertebral Heart Score for Dilated Cardiomyopathy in Dogs - Parmar, Saurabh M.; Patel, Manish D.; Jhala, Shivraj K.; Suthar, Dipak. N.; Vala, Jignesh A.; Mehta, Sushir A.; Mavadiya, Suresh V. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was aimed to use vertebral heart score for confirmatory diagnosis of suspected dilated cardiomyopathy (DCM) in  dogs (n=18) among 6366 dogs presented at College Clinic, Navsari, Gujarat, over a period of two years. The most common symptoms  in dogs suspected of cardiac diseases (n = 56) were exercise intolerance, dyspnoea, weakness, coughing, inappetence, weight loss,  abdominal enlargement, vomiting, and syncope. Suspected cases of cardiac abnormalities were screened for confirmatory diagnosis  of dilated cardiomyopathy, which revealed 18 patients with DCM. The vertebral heart size was measured as the sum of the long-axis  and short-axis at its greatest diameter and then compared with the vertebra bones starting at T4. The vertebral heart score in dilated  cardiomyopathy-affected dogs was found significantly (p
Keywords: Diagnostic tool; Dilated cardiomyopathy; Dogs; Vertebral heart score